From hand tillage to animal traction: Causes and effects and the policy implications for sub-Saharan African agriculture - Pingali, Prabhu L. (International Livestock Centre for Africa, 1987)
Identifies conditions affecting the transition from hand tillage to animal traction and further transition to tractors. Asseses causes, effects and policy implications for sub-Saharan African agriculture.